Morphology-Dependent Antioxidant Activity of Gold Nanoparticles Prepared Using Different Electrolyte Concentrations - Abd Aziz, Azri Farhanah; Suliasih, Babay Asih (Pusat Inovasi Sains, 2025)
Antioxidants play a crucial role in protecting the body from oxidative stress by neutralizing free radicals. The synthesis of antioxidant-active materials, such as gold nanoparticles (AuNPs), offers significant advantages due to their unique physicochemical properties. In this study, AuNPs were successfully synthesized using the electrodeposition method on indium-tin oxide substrates, with varying Na₂SO₄ electrolyte concentrations. Scanning electron microscopy analysis confirmed that the synthesized AuNPs exhibited a round to slightly irregular morphology, with an average particle size ranging from 48 to 65 nm. X-ray diffractometer characterization revealed that the nanoparticles possessed a face-centered cubic crystal structure, confirming their high purity. Antioxidant activity was evaluated using the DPPH assay, where AuNPs synthesized with 0.5 M Na₂SO₄ exhibited the highest DPPH inhibition of 72.39%. This enhanced antioxidant performance is attributed to the smaller particle size, which increases the available surface area for free radical neutralization. These findings highlight the potential of electrodeposited AuNPs as effective antioxidants and provide valuable insights into optimizing nanoparticle synthesis for biomedical and nanotechnological applications.